Indications for surgery versus conservative treatment in the management of lumbar disc herniations: A systematic review - Santhosh G. Thavarajasingam; Ahmed Salih; Aksaan Arif; Madhur Varadpande; Pratheeshan Sabeshan; Hariharan Subbiah Ponniah; Sree Kanakala; Srikar R. Namireddy; Daniele S.C. Ramsay; Ahkash Thavarajasingam; Daniel Scurtu; Dragan Jankovic; et al. (Brain and Spine, 2025)
Introduction: Lumbar disc herniation (LDH) is a leading cause of radiculopathy and low back pain, contributing significantly to global disability. Management strategies include conservative and surgical treatments, but clinical decision-making lacks standardization, particularly in surgical indications, timing, and criteria for transitioning from conservative management. Research question: What are the surgical indications, criteria for transitioning from conservative to surgical management in LDH, and what role do motor deficits play? Material and methods: Following PRISMA guidelines, a systematic search across major databases identified 20 studies. Risk of bias was assessed using the Newcastle Ottawa Scale and RoB 1 tools. A qualitative synthesis was conducted, and the Index of Qualitative Variation (IQV) quantified variability in indications. Results: Among the studies that reported specific indications, imaging-confirmed nerve root compression (reported in 18/20 studies) and severe/refractory pain (reported in 17/20 studies) were the most consistent indications, while thresholds for sensory deficits (reported in 8/20 studies) varied widely. Early surgery (48 h–6 weeks) was associated with superior recovery, particularly for mild/moderate motor deficits graded ≤ MRC 3/4, achieving >90 % recovery rates. Delayed surgery (>6 weeks) resulted in prolonged symptoms and poorer outcomes, especially in severe cases. Transition criteria included a patient-specific combination of failure of conservative therapy (n = 12) after a most frequently 4–6-week trial, neurological progression, and worsening imaging findings. Significant heterogeneity was observed in thresholds for motor and sensory deficits, with high IQV scores for definitions of conservative treatment failure (IQV = 0.96) and motor deficit (IQV = 0.96). Discussion and conclusion: Significant heterogeneity in surgical indications, timing, and decision-making highlights the urgent need for standardized, evidence-based guidelines to optimize clinical decisions and improve outcomes in LDH management.